2021
DOI: 10.14701/ahbps.2021.25.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Model for End-Stage Liver Disease allocation system on outcomes of deceased donor liver transplantation: A single-center experience

Abstract: Backgrounds/Aims: From June of 2016, the Model for End-Stage Liver Disease (MELD)-based allocation system replaced the Child-Turcotte-Pugh (CTP) score-based system for organ allocation liver in Korea. The aim of this study was to analyze changes in outcomes and arising issues before and after the implementation of the MELD system. Methods: From June 2014 to June 2018, 129 patients were selected from recipients who underwent deceased donor liver transplantation (DDLT) in Seoul National University Hospital. Pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The reasons for the difference in mortality rate between the 2 groups were related to the higher proportion of alcoholic liver cirrhosis patients in the post-MELD group and the MELD score difference between the 2 groups. A recent study reported that 6-month mortality in pre-MELD group (n = 77) and post-MELD group (n = 52) were 11.7% and 25.0%, respectively (P = 0.022) [ 14 ]. In multivariate analysis [ 14 ], MELD/CTP allocation was the only factor that showed significant association with higher 6-month mortality than the CTP allocation system (HR, 2.865; 95% CI, 1.057–7.764; P = 0.039).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the difference in mortality rate between the 2 groups were related to the higher proportion of alcoholic liver cirrhosis patients in the post-MELD group and the MELD score difference between the 2 groups. A recent study reported that 6-month mortality in pre-MELD group (n = 77) and post-MELD group (n = 52) were 11.7% and 25.0%, respectively (P = 0.022) [ 14 ]. In multivariate analysis [ 14 ], MELD/CTP allocation was the only factor that showed significant association with higher 6-month mortality than the CTP allocation system (HR, 2.865; 95% CI, 1.057–7.764; P = 0.039).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that 6-month mortality in pre-MELD group (n = 77) and post-MELD group (n = 52) were 11.7% and 25.0%, respectively (P = 0.022) [ 14 ]. In multivariate analysis [ 14 ], MELD/CTP allocation was the only factor that showed significant association with higher 6-month mortality than the CTP allocation system (HR, 2.865; 95% CI, 1.057–7.764; P = 0.039). However, MELD score and organ ischemic time were classified as risk factors for 6-month mortality rate in the current study.…”
Section: Discussionmentioning
confidence: 99%